Evaluation of six different types of sequential conditioning regimens for allogeneic stem cell transplantation in relapsed/refractory acute myelogenous leukemia – a study of the Acute Leukemia Working Party of the EBMT. Issue 2 (28th January 2021) - Heinicke, Thomas; Labopin, Myriam; Polge, Emmanuelle; Stelljes, Matthias; Ganser, Arnold; Tischer, Johanna; Brecht, Arne; Kröger, Nicolaus; Beelen, Dietrich W.; Scheid, Christof; Bethge, Wolfgang; Dreger, Peter; et al.
Abstract: The Acute Leukemia Working Party (ALWP) of the EBMT assessed the outcome of allogeneic stem cell transplantation (alloSCT) in patients with relapsed/refractory AML (r/rAML) evaluating six sequential conditioning regimens (SR) groups. A total of 2132 patients were included. LFS at 2 years was 28.9%, 33.6%, 35.3%, 20.6%, 24.4%, and 27% for the FLAMSA-TBI4, FLAMSA-Chemo, Mel-Flu-TBI8, Mel-Treo-Flu, Thio-ETO-Cy-Bu2-Flu, and Clo-ARAC-(Bu2/TBI4)-Cy groups, respectively. In patients <55 years of age Mel-Flu-TBI8 had the best LFS, which was statistically significant only in comparison to the Mel-Treo-Flu group, while in patients ≥55 years LFS was best with FLAMSA-Chemo without significant differences compared to FLAMSA-TBI4 and Mel-Flu-TBI8. Furthermore, best NRM rates were obtained with the two FLAMSA regimens groups. Our study suggests that in younger (<55 years) patients a more intense regimen might be used whereas in older (≥55 years) patients the focus might be more on tolerability.